2009
DOI: 10.1111/j.1528-1167.2008.01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the MDR1/ABCB1 C3435T drug‐transporter and resistance to anticonvulsant drugs: A meta‐analysis

Abstract: SUMMARYBackground: Approximately one-third of patients with epilepsy patients have recurrent seizures despite therapy. It has been suggested that therapeutic failure is associated with high expression of the multidrug efflux ABCB1 (MDR1) drug-transporter; specifically, that patients with the 3435CC genotype have higher efflux of anticonvulsants out of brain tissue, with correspondingly lower concentrations in the central nervous system. Methods: We conducted a meta-analysis to examine the association between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 27 publications
(79 reference statements)
1
78
2
2
Order By: Relevance
“…39 Further, it has been suggested that drug refractory epilepsy may be related to gain-of-function ABCB1 SNPs. [40][41][42][43][44] In experimental models, ABCB1, predominantly expressed in brain microvessels at baseline, 45 is reduced 2 months after controlled cortical impact in juvenile rats. 46 Our data did not reveal differences between relative protein levels of ABCB1 in TBI versus controls; however, this could be because of the limited sample size and/or the fact that the average time from injury to biopsy was 37 h.…”
Section: Abcc1 and Abcb1 In Human Brain After Severe Tbimentioning
confidence: 99%
“…39 Further, it has been suggested that drug refractory epilepsy may be related to gain-of-function ABCB1 SNPs. [40][41][42][43][44] In experimental models, ABCB1, predominantly expressed in brain microvessels at baseline, 45 is reduced 2 months after controlled cortical impact in juvenile rats. 46 Our data did not reveal differences between relative protein levels of ABCB1 in TBI versus controls; however, this could be because of the limited sample size and/or the fact that the average time from injury to biopsy was 37 h.…”
Section: Abcc1 and Abcb1 In Human Brain After Severe Tbimentioning
confidence: 99%
“…Several recent meta analyses of studies investigating the c.3435C>T polymorphism are listed in table 3. Digoxin pharmacokinetics were not affected by c.3435C>T [98] and the response to anticonvulsant drugs exhibited also no association with this polymorphism [99,100]. In contrast, the effects on cyclosporine pharmacokinetics are more complex: Overall, there was no effect of the c.3435C>T ABCB1 polymorphism on the pharmacokinetic parameters, although the total cyclosporine bioavailability (AUC 0-12 ) was slightly reduced (table 3) [101].…”
Section: Mdr1 (Abcb1)mentioning
confidence: 87%
“…Epilepsy patients with the CC genotype had lower levels of phenobarbital in the CSF and exhibited higher seizure activity [72]. The first study, in 2003, suggested that the 3435C > T polymorphism may explain resistance to AED therapy in epilepsy [73], but several other association studies, as well as meta-analyses, have clearly demonstrated that the impact of ABCB1 genetics on the pharmacoresistance of AEDs is inconsistent [62,74,75]. However, the concept that Pgp expression and function may be directly associated with pharmacoresistant temporal lobe epilepsy in patients has been very recently corroborated by a highly attractive approach investigating Pgp activity in patients with epilepsy using positron emission tomography technology [76].…”
Section: Role Of Drug Distribution For Pharmacoresponsementioning
confidence: 99%